Prediction of long-term survival in gastric cancer patients after immunotherapy based on CT-derived extracellular volume fraction - Wang, Yuyang; Jiang, Shanshan; Yang, Yanjie; Li, Yi; Li, Zhiying; Lei, Ziqiao; Kong, Xiangchuang; Zhou, Guofeng (Frontiers in Oncology, 2025)
BackgroundGastric cancer remains a leading cause of cancer-related mortality. While immune checkpoint inhibitors (ICIs) have emerged as promising therapies, their efficacy is hindered by the lack of robust patient-centric biomarkers. CT-derived extracellular volume fraction (ECV) has emerged as a novel approach for non-invasive quantification of the extracellular matrix (ECM). This study assesses the predictive value of ECV, a non-invasive imaging biomarker, in gastric cancer patients receiving programmed death receptor-1 (PD-1) inhibitors.MethodsA retrospective study was conducted on 101 gastric adenocarcinoma patients (stage III: n = 47; stage IV: n = 54) treated with PD-1 inhibitors at Wuhan Union Hospital from June 21, 2020 to January 3, 2024. The patients were stratified into high- and low-ECV groups using X-tile software. Survival outcomes were compared using Kaplan–Meier curves and log-rank tests. Cox regression analyses identified independent prognostic factors. Two predictive models were developed and evaluated via receiver operating characteristic (ROC) curves and area under the curve (AUC), with internal validation using 1,000 bootstrap iterations.ResultsKaplan–Meier survival curves indicated that the ECV-higher group had shorter progression-free survival (PFS) (P < 0.001) and overall survival (OS) (P < 0.001) than the ECV-lower group. Multivariate Cox regression analysis confirmed that high CT-ECV was independently associated with worse PFS and OS (PFS: HR = 2.716, 95% CI: 1.432–5.152, P = 0.002 and OS: HR = 2.593, 95% CI: 1.322–5.084, P = 0.006).ConclusionCT-derived ECV may serve as an independent predictor of long-term survival in gastric cancer patients undergoing immunotherapy.